FETAL ABDOMINAL OBESITY AND ADVERSE PERINATAL OUTCOMES IN OLDER AND OBESE PREGNANT WOMEN WITH NORMAL GLUCOSE TOLERANCE - Kim, Wonjin (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION We previously observed an increased prevalence of fetal abdominal obesity (FAO) in older with/without obese women with gestational diabetes mellitus. We investigated whether the increased risk of FAO was also present in older with/without obese women with normal glucose tolerance (NGT). METHODOLOGY We retrospectively reviewed 6,721 individuals with NGT, diagnosed by 50-g glucose challenge test (GCT) <140 mg/dL or normal subsequent 100-g oral glucose tolerance test if GCT ≥140 mg/dL. FAO was investigated ultrasonographically using ratios of gestational age with abdominal circumference, biparietal diameter, and femur length. The NGT subjects were divided into group 1 (age<35 years and pre-pregnant body mass index (BMI) <25 kg/m2 ), group 2 (age<35 & BMI≥25), group 3 (age ≥35 and BMI <25), and group 4 (age ≥35 and ≥25). RESULTS FAO ratios of groups 3 and 4 were significantly higher than group 1. Relative to group 1, the adjusted odds ratio for FAO in group 3 was 1.42 (95% CI; 1.17-1.73, p <0.05), and in group 4 was 1.90 (1.15-3.15, p <0.05). The odds ratio for large gestational age (LGA) at birth, relative to group 1, were 3.06 (1.96-4.77, p <0.005), 1.47 (1.16-1.86, p <0.005), and 2.82 (1.64-4.84, p <0.005) in group 2, 3 and 4, respectively. The odds ratio for primary cesarean delivery in group 3 was 1.33 (1.18-1.51, p <0.005). CONCLUSION Increased risk of FAO at 24-28 GW and the ensuing adverse perinatal outcomes of LGA and primary cesarean delivery were observed in the older with/without obesity but not in the younger/non-obese NGT women.